Is it my fault? The role of the feeling of guilt in adolescent peer victimization - León-Moreno, Celeste; Suárez-Relinque, Cristian; Callejas-Jerónimo, Juan Evaristo; García-Vázquez, Fernanda Inéz (Frontiers in Psychology, 2023)
Introduction The aim of this study was to analyze the relationships between feelings of guilt, peer victimization in school, and loneliness based on adolescents’ gender. Methods A total of 671 Spanish students (50.7% boys), aged 10–16 years old (M = 13.04, SD = 1.80) from six public primary and secondary schools participated in the study. A Multivariate Analysis of Variance (3 × 2) was calculated. Results Adolescents with high levels of guilt presented greater physical, verbal, and relational victimization, as well as higher levels of loneliness. In addition, boys high in guilt had the highest scores in overt physical victimization, while girls high in guilt had the highest levels of loneliness. Discussion Results obtained suggest that adolescents with greater feelings of guilt feel responsible for being victims of peer aggression and for feeling lonely. These findings suggest the need to address the feeling of guilt, taking into account the gender perception.